Penilaian Risiko Ergonomi pada Pekerja Pembuatan Kue-Kue Basah terhadap Keluhan Musculosketal Disorders - Samira Samira; Pitri Noviadi; Diah Navianti; Intan Kumalasari; Maya Sopianti (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Musculoskeletal Disorders (MSDs) complaints in muscles, joints, and soft tissues can be caused by poor posture, repetitive movements, and excessive physical load. In the wet cake-making industry, workers often sit or stand for long periods, bend, and perform monotonous hand movements, which increases the risk of MSDs. The impact includes decreased work comfort, productivity, and quality of life. This study aims to assess the ergonomic risk level in wet cake-making workers and identify the relationship between work activities and MSD complaints. The method used is descriptive quantitative research with a cross-sectional design, involving 45 workers at Kue X Silaberanti. Ergonomic risk was assessed using the REBA method, while MSD complaints were measured using the Nordic Body Map questionnaire. The results show that in the mixing process, 58.8% of workers experienced a very high risk of MSDs. In the molding and baking processes, 52.9% and 68.8% of workers, respectively, were at high risk. The most frequent complaints were pain in the back, neck, shoulders, arms, and wrists due to poor posture and repetitive movements. To reduce the risk of MSDs, workers need to improve their posture, use ergonomic aids, rotate tasks, and undergo training in safe working techniques.